Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages Factories Act very feebly mentions that young persons must not lift weights too heavy for them. But Home Office Safety Pamphlet No.16 (Weight lifting by Industrial Workers — H.M. Stationery Office, 1/3d.) deals with the whole question of weight lifting in the most satisfactorily complete manner. The chief causes of accidents under this head are: (1) Joint Lifting, i.e., the multiplication of man-power to divide the load. Inquiry has shown that in 28 per cent of weight lifting accidents in men, joint lifting was being attempted. The common faults are for the load not to be fairly shared and for the effort not to be evenly synchronized; two common faults, by the way, in all manner of activities apart from weight lifting. (2) The load is too heavy compared with the weight and strength of the person moving it. Hence the load is liable to take charge. (3) Mechanical appliances are not used enough. There is a very big scope for simple inventions here in many factories; for example, in munitions factories where shells are being much handled. The standard as to what are exactly the best and safest loads to handle is not easy to define and might well be the subject of further research. The Home Office pamphlet gives the following standard of maximum loads: Men 130 lbs Compact load Women 65 lbs (Intermittent work) 50 lbs (Continuous work)* Young Persons of 16-18 years Male 60 lbs (Intermittent work) 45 lbs (Continuous work)* Female 56 lbs (Intermittent work) 40 lbs (Continuous work)* Young Persons of 14-16 years...... Male 35-40 lbs Female 35-40lbs *The term "Continuous lifting" is used to denote lifting of one ton or more a day. A load of 40 lbs. lifted 7 times per hour for 8 hours totals one ton. 18 21/2049